The Effect the Canva Based Problem Based Learning Model on Student Motivation and Learning Outcomes in Science and Technology Subjects - Mutiara Prihatiningtyas; Tri Astuti (Jurnal Penelitian Pendidikan IPA, 2024)
Classroom learning that is only limited to listening, doing assignments, and only focusing on books and teachers causes the learning process to be passive. This results in low achievement of learning outcomes and lack of learning motivation in students. The purpose of this study is to explore the impact of using a canva-based problem-based learning model on the motivation and learning outcomes of grade V students in IPAS subjects at SDN Tugurejo 01. This study adopted a quantitative approach with a quasi-experimental method using a nonequivalent control group research design. Data collection was done through observation, tests, questionnaires, and documentation. The results showed a significant difference in learning outcomes and student motivation between the use of a canva-based problem-based learning model and conventional teacher-centered learning. Hypothesis testing using independent T-test shows the significance value of learning outcomes is 0.004, which means <0.05, so H0 is rejected and H1 is accepted. Similarly, in learning motivation, the Sig (2-tailed) value is 0.031, which means <0.05, meaning H0 is rejected and H1 is accepted. From the results of this study, it can be concluded that the canva-based problem-based learning model has a positive influence on student motivation and learning outcomes in class V IPAS subjects at SDN Tugurejo 01.